2016
DOI: 10.1002/1873-3468.12121
|View full text |Cite
|
Sign up to set email alerts
|

Attacking the supply wagons to starve cancer cells to death

Abstract: The constitutive anabolism of cancer cells supports proliferation but also addicts tumor cells to a steady influx of exogenous nutrients. Limiting access to metabolic substrates could be an effective and selective means to block cancer growth. In this review, we define the pathways by which cancer cells acquire the raw materials for anabolism, highlight the actionable proteins in each pathway, and discuss the status of therapeutic interventions that disrupt nutrient acquisition. Critical open questions to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 231 publications
(309 reference statements)
0
63
0
Order By: Relevance
“…Our results showed that SRPK2 inhibition with lipid deprivation inhibits cancer cell proliferation (Figure 7). Therefore, combination therapies using specific SRPK2 inhibitors and lipid uptake blockers such as CD36 antibodies (Pascual et al, 2016; Selwan et al, 2016) would also be a promising regimen for treatment of cancers with high dependency on mTORC1 signaling and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that SRPK2 inhibition with lipid deprivation inhibits cancer cell proliferation (Figure 7). Therefore, combination therapies using specific SRPK2 inhibitors and lipid uptake blockers such as CD36 antibodies (Pascual et al, 2016; Selwan et al, 2016) would also be a promising regimen for treatment of cancers with high dependency on mTORC1 signaling and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…How SH-BC-893 administration affects whole-body metabolism and cytokine levels merits further investigation. As a single agent, SH-BC-893 acts like a combination therapy by targeting the multiple nutrient acquisition pathways that fuel cancer anabolism (17). It will be important to test whether pairing SH-BC-893 with drugs that target oncogenic signal transduction pathways will increase efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…The following antibodies were used: murine 4F2HC (catalog 128208; eBioscience) and LAMP1 (catalog 53-1079-42; eBioscience); human 4F2HC (catalog 556077; BD Biosciences); human GLUT1 (catalog NB300-666; Novus Biologicals); LC3 (catalog 4108; Cell Signaling Technology); PIKfyve (catalog 4082; Tocris); VAC14 (catalog SAB4200074; Sigma-Aldrich); and WIPI2 (catalog LS-C154557-100; LifeSpan Biosciences). Colocalization was determined using the JACoP plugin in ImageJ software (NIH (17). The development of resistance limits the effectiveness of targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations